Digital Revolution in HR: AR Implementayion for Employee Training and Recruitment - Anike Retawati; Achmad Syamsudin; Muhammad Ruzaini Abdi (Universitas Muhammadiyah Palu, 2025)
This research examines the implementation of Augmented Reality (AR) technology in the employee training and recruitment process at Dicoding Indonesia. The purpose of this research is to evaluate the effectiveness, challenges, and opportunities of using AR in improving training interactivity and supporting the recruitment process of digital talents. The approach used was qualitative with a case study method. Data was collected through in-depth interviews, direct observation, and analysis of Dicoding's internal documents. The results showed that the implementation of AR in training increased the interactivity and engagement of participants, and helped in the development of practical skills. However, there were technical challenges related to AR devices and difficulties in integrating the technology with training materials. On the recruitment side, AR provided a more realistic simulation experience for prospective employees, which improved the effectiveness of their practical skills assessment. This research suggests further development of AR technology in Dicoding and other companies as a solution to improve efficiency and effectiveness in training and recruitment.